MODELING OF UPWELLING AND COLLAPSE IN THE SEEPAGE FLOW OUTLET ZONE ON THE SLOPE OF THE CHIMKURGAN RESERVOIR - Eshkuvatov , Kuvonchbek (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article examines water seepage processes in the dam body and on the slope of the Chimkurgan Reservoir, as well as modeling upwelling and potential soil collapse in the seepage outlet zone. Based on theoretical principles of hydrodynamics and soil mechanics, an analysis of the conditions for the formation of seepage pressure and critical hydraulic slope is provided. Using mathematical modeling and geoinformation technologies, seepage flow distribution patterns are investigated, and potentially hazardous zones of upwelling and reduced slope stability are identified. The stability coefficient is estimated taking into account the influence of pore pressure and hydraulic loads. The obtained results allow us to predict the development of seepage deformations and justify engineering measures to improve the reliability of the hydraulic structure. The practical significance of this work lies in the potential use of the proposed method for monitoring and preventing emergency situations at reservoirs.